Utility of the Charlson Comorbidity Index Computed from Routinely Collected Hospital Discharge Diagnosis Codes - O’Connell, R. L.; Lim, L. L.-Y. (Methods of Information in Medicine, 2000)
This study aims to determine whether the Charlson comorbidity index computed from ICD-9-CM discharge diagnosis codes adds additional information to a model containing adjustment for more informed patient details (e.g., disease severity and history), besides solely age and sex, when predicting long-term survival. We conducted a retrospective cohort study of patients admitted to hospital for suspected acute myocardial infarction. Index scores were calculated by applying the D’Hoore et al. algorithm (1993). The index significantly improved the model fit (likelihood ratio test: p <0.001). The D’Hoore-adapted Charlson index is a useful comorbidity risk adjustment tool when applied to AMI and angina patients.
Keywords: Comorbidity; Risk Adjustment; Acute Myocardial Infarction; Mortality